A feminização do trabalho docente em Roraima: o Curso Normal Regional Monteiro Lobato nos jornais "O átomo" e "Boa Vista" (1949-1964) - Silva, Rosielma Barroso da (2022)
This research aims to analyze the discourses of political, social and economic institutions regarding the social role of women in the Normal Regional Course Monteiro Lobato (CNRML), found in the newspapers “O Átomo” and “Boa Vista” and in the institution's own documents. We used a qualitative methodological approach based on documentary research, in which the selected documents were analyzed according to the Content Analysis Theory founded by Laurence Bardin (1977). For theoretical development, we discussed the categories: work, education and gender, in which the last two presented subcategories, respectively, teacher professionalization and feminization. With the aid of the theoretical-methodological contribution, we analyzed the newspapers “O Átomo” and “Boa Vista”, as well as the CNRML documents, which present dual methodological aspects, being subjects and objects of the investigation. The analysis categories were defined as: Church-State fusion, feminine spaces, stereotypes about being a woman, civic aspects in the teachers' performance and transgression of stereotypes (for newspaper analysis) and the categories: work, education, gender and feminization of work teacher (for analysis of CNRML documents/laws). The discourses about being a woman in the Federal Territory of Rio Branco (TFRB), in the 1940s and 1950s, pointed to a woman who should be a mother-wife-docile-selfless-patriot, for this reason the teachers exercised teaching in this ambiguity, teaching children to love God and Country. The process of feminization of teaching work was permeated by contradictions, dualities and uncertainties in which women performed their functions as teachers in the face of a profession marked by discourses about femininity, but at the same time they became protagonists of their stories, marking the rio-branquense teaching profession, seeing in teaching the possibility of changing their lives.